KEPEMIMPINAN SPIRITUAL KEPALA SEKOLAH PONDOK PESANTREN MODERN SHOHWATUL IS’AD (STUDI KASUS PADA SMP IT SHOHWATUL IS’AD MA’RANG KAB. PANGKEP) - Daiman, Suryawati Ningsih (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2018)
This research aims to know the three things regarding the execution of the Spiritual leadership of the principal Modern boarding schools Shohwatul Is'ad (case study on Junior High School IT Shohwatul Is'ad Ma'rang Kab. Pengkep). Besides the goal of this research is to find out which (i) the implementation of spiritual leadership style. (ii) the strengths and values of the dominant spiritual leadership which led into a model of effective leadership in developing educational and learning organizations and (iii) the driving factor and a barrier to implementation leadership spiritual. The methods used in this studying using qualitative research methods which researchers working to understand, describe, explain the theory and qualitative instruments in the form of what is gained from the field research. The results showed: (1) the application of spiritual leadership still hasn't been fullest and still requires a process and the hard work of the leaders and all the stakeholders.  (2) factor endowments and a barrier to implementation of spiritual leadership style. (a) which is a factor supporting IE; the condition of the lingkunag institution, appropriate institutions with the vision of the leadership style of spiritual openness by all teachers to menerimah style kepemimpnan spiritual. (b) the factors restricting namely; do not tirciptanya the culture of the school, working principles that are still transactional so that efforts to develop the institutions still krang and, still the least effort applying spiritul values by teachers in running the function meskipin in the concept has to understand.